a A PLAN FOR DEALING WITH THE OCCURRENCE AND SPREAD OF INFECTIOUS DISEASES CAUSED BY THE CORONAVIRUS AND THE ROLE OF THE OCCUPATIONAL MEDICINE SERVICE - Milenković, Ivona (Acta medicae Medianae, 2023)
The plan for the application of preventive measures against occurrence and spread of infectious diseases is valid for all workplaces and in the work environment of the organization and is implemented in order to prevent epidemics of infectious diseases and eliminate risks to safe and healthy work of employees. The aim of this paper was to point out the importance of the existence of a plan for the implementation of preventive measures against occurrence of infectious diseases and the role of the occupational medicine service in the implementation of this plan. The results of the paper present the experiences in the implementation of preventive measures in the event of an epidemic of infectious diseases caused by the coronavirus and the method of treatment of patients with this disease. The views and activities of the occupational medicine service in the case of work ability assessment in persons after a previous illness and declaring the disease caused by the coronavirus an occupational disease were presented. It was concluded that it is extremely important to act according to the established plan.
Keywords: infectious disease, ability to work, COVID-19, occupational disease